Level of Psychological Burnout among the Health Staff in the COVID-19 Isolation Department, in the Light of Some Variables Field study in Martyr Iyad Ibrahim Hospital (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The objective of this study is to know the level of psychological burnout  among the health staff in the COVID-19  isolation department, Martyr Iyad Ibrahim Hospital in the city of Baniyas, and identify the differences in the level of psychological burnout by (sex, age, type of employment, and years of service variables).The sample of the study consisted of (39) doctors and nurses of males and females, (13) doctors, (26) nurses.To achieve the aim of the study, the researcher used the descriptive analytical approch, and the measure of Maslach Burnout which consists of (22) items, after it was judged and modified to fit the current study- The study showed the following results:- The level of psychological burnout for the health staff in the COVID-19 Isolation Department, Martyr Iyad Ibrahim Hospital was ( 33,33%) medium and (66,67%) high- And the results did not show statistical significant differences in Psychological Burnout among the sample members according to the variables, (sex, age, type of employment, and years of service).